AIP Conference Proceedings 2009
DOI: 10.1063/1.3180054
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of mixtures of circular and rectangular 2D particles

Abstract: This paper presents the results of experimental compression tests on a 2D granular material composed of a mixture of circular and rectangular rods. Numerical simulations of the tests, using a Discrete Element Method (Molecular Dynamics), successfully reproduce the experimental results. The results of the comparison between experimental and numerical results highlights the important role of the contact laws (especially the rolling resistance). A statistical study of the rotations of rectangular particles during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Since the experiments of Oda [3] performed on assemblies of oval cross-sectional rods, several studies have been reported and rather recent results suggest that assemblies of non-spherical particles exhibit higher shear strength than sphere packings and may approach unusually high packing fractions [2,4,5,6]. However, such results are often limited to a specific shape parameter, such as angularity with polygonal particles [7,8,9], elongation with ellipsoids or elongated faceted particles [10,11,12,13,14,15], or nonconvexity [16,17,18]. Moreover the effect of each of these parameters is experimentally difficult to investigate in a systematic way.…”
Section: Introductionmentioning
confidence: 87%
“…Since the experiments of Oda [3] performed on assemblies of oval cross-sectional rods, several studies have been reported and rather recent results suggest that assemblies of non-spherical particles exhibit higher shear strength than sphere packings and may approach unusually high packing fractions [2,4,5,6]. However, such results are often limited to a specific shape parameter, such as angularity with polygonal particles [7,8,9], elongation with ellipsoids or elongated faceted particles [10,11,12,13,14,15], or nonconvexity [16,17,18]. Moreover the effect of each of these parameters is experimentally difficult to investigate in a systematic way.…”
Section: Introductionmentioning
confidence: 87%
“…1, located in 3SR Laboratory in Grenoble, France. The apparatus was used and described numerous times (Joer et al [6]; Calvetti et al [1]; Sibille and Froiio [11]; Hall et al [5]; Lirer et al [7]; Charalampidou et al [3]). 1γ2ε is able to impose different plane stress loading conditions on 2D analogue Schneebeli material (Schneebeli [10]).…”
Section: Experimental Programmentioning
confidence: 99%
“…Shear tests have been performed in the 1γ2ε apparatus, which is essentially a plane stress version of the directional shear cell developed for testing soils (see [1,9,10] for details). Results from only one such test are discussed herein, although the results are consistent throughout the entire campaign.…”
Section: Shear Testmentioning
confidence: 99%